Just Another Cog in the Machine? A Worker-Level View of Robotization and Tasks - Milena Nikolova; Anthony Lepinteur; Femke Cnossen (Institute of Labor Economics (IZA), 2023)
Using survey data from 20 European countries, we construct novel worker-level indices of routine, abstract, social, and physical tasks, which we combine with industry-level robotization exposure. Our conceptual framework builds on the insight that robotization simultaneously replaces, creates, and modifies workers' tasks and studies how these forces impact workers' job content. We rely on instrumental variable techniques and show that robotization reduces physically demanding activities. Yet, this reduction in manual work does not coincide with a shift to more challenging and interesting tasks. Instead, robotization makes workers' tasks more routine, while diminishing the opportunities for cognitively challenging work and human contact. The adverse impact of robotization on social tasks is particularly pronounced for highly skilled and educated workers. Our study offers a unique worker-centric viewpoint on the interplay between technology and tasks, highlighting nuances that macro-level indicators overlook. As such, it sheds light on the mechanisms underpinning the impact of robotization on labor markets.
Keywords: J01; J30; J32; J81; I30; I31; M50; 330; worker-level data; technological change; robotization; tasks